2014
DOI: 10.1108/bfj-01-2014-0046
|View full text |Cite
|
Sign up to set email alerts
|

Tourist perceived image of local cuisine: the case of Bosnian food culture

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 36 publications
(56 reference statements)
4
79
3
3
Order By: Relevance
“…Furthermore, there are three main indicators constructing the culinary experience quality (CEQ), they are: the ambience of the dining place (CEQ-P2), the unique food presentation (CEQ-F5) and the local people's hospitality (CEQ-S4). This finding is in accordance with the previous studies that the three major dimensions to measure the quality of culinary experience with local food at a destination are food dimension (food uniqueness), social dimension (local people's hospitality) and place and time dimension (ambience) (Hendijani et al, 2013, Peštek and Činjarević, 2014, Wijaya et al, 2017.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, there are three main indicators constructing the culinary experience quality (CEQ), they are: the ambience of the dining place (CEQ-P2), the unique food presentation (CEQ-F5) and the local people's hospitality (CEQ-S4). This finding is in accordance with the previous studies that the three major dimensions to measure the quality of culinary experience with local food at a destination are food dimension (food uniqueness), social dimension (local people's hospitality) and place and time dimension (ambience) (Hendijani et al, 2013, Peštek and Činjarević, 2014, Wijaya et al, 2017.…”
Section: Discussionsupporting
confidence: 92%
“…Contrary from the previous study, the main satisfier indicator of culinary experience satisfaction is the quality of the dining place (CES3) instead of the food quality by Peštek and Činjarević (2014). It means that the satisfaction of the participants who were international tourists was basically determined more by the dining place quality than the food quality.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, the results of this current study also accords with the previous study. That is, food quality appeared to be the main satisfier indicator of culinary experience satisfaction (CES1) [22]. However, this finding is in contrast with the previous study done to the international tourists in Denpasar and Yogyakarta in which it was found that their satisfaction with the culinary experience was mainly determined by the dining place quality instead of the food quality [21].…”
Section: Discussionmentioning
confidence: 57%
“…Efficient government management has a positive effect on economic impacts, and governmental tourism management and planning are crucial for residents' satisfaction. The current government structure in B&H and the FB&H suffers from a lack of vertical and horizontal coordination amongst institutions, and is considered to be the factor hampering the development of the national economy, including the tourism sector (Peštek & Činjarević, 2014). In the absence of a national and entity policy for tourism development, it is difficult to formulate effective development strategies in B&H and the FB&H. Over previous years, development activities in tourism have been managed in an uncoordinated manner without a strategic long-term orientation.…”
Section: Resultsmentioning
confidence: 99%